Current perspectives of mitochondria-targeted antioxidants in cancer prevention and treatment - Zinovkin, Roman A.; Lyamzaev, Konstantin G.; Chernyak, Boris V. (Frontiers in Cell and Developmental Biology, 2023)
Oxidative stress nearly always accompanies all stages of cancer development. At the early stages, antioxidants may help to reduce reactive oxygen species (ROS) production and exhibit anticarcinogenic effects. In the later stages, ROS involvement becomes more complex. On the one hand, ROS are necessary for cancer progression and epithelial-mesenchymal transition. On the other hand, antioxidants may promote cancer cell survival and may increase metastatic frequency. The role of mitochondrial ROS in cancer development remains largely unknown. This paper reviews experimental data on the effects of both endogenous and exogenous antioxidants on cancerogenesis focusing on the development and application of mitochondria-targeted antioxidants. We also discuss the prospects for antioxidant cancer therapy, focusing on the use of mitochondria-targeted antioxidants.